Ofatumumab, a fully human anti-CD20 monoclonal antibody, in biological-naive, rheumatoid arthritis patients with an inadequate response to methotrexate: a randomised, double-blind, placebo-controlled clinical trial. - Taylor, P; Quattrocchi, E; Mallett, S; Kurrasch, R; Petersen, J; Chang, D (2011)
To evaluate the efficacy and safety of intravenous ofatumumab, a fully human anti-CD20 monoclonal antibody, in biological-naive, active rheumatoid arthritis (RA) patients despite methotrexate treatment.